Results of the laparoscopic lateral suspension and laparoscopic sacrocolpopexy techniques done for uterine prolapse: Comparison of two laparoscopic methods for uterine prolapse - Satır Özel , Canan; Küçükbaş , Mehmet; Yardımcı , Oğuz Devrim; Nalbant , Vildan; Karateke , Ateş (Journal of Surgery and Medicine, 2024)
Background/Aim: Sacrocolpopexy is considered the gold-standard surgical treatment for patients with symptomatic uterine prolapse. This technique can be performed using a laparoscopic approach. Laparoscopic lateral suspension has emerged as a new alternative pelvic organ prolapse surgery method. This study aims to compare the postoperative anatomical improvement and sexual function outcomes in patients who underwent laparoscopic sacrocolpopexy (Group 1) versus laparoscopic lateral suspension (Group 2) for pelvic organ prolapse at our institution. Methods: Group 1 consisted of 14 patients, while Group 2 comprised seven patients. Relevant data were collected using the Turkish-validated Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12), A Simple Questionnaire to Screen for Sexual Dysfunction, and the Pelvic Organ Prolapse Quantification System (POP-Q) questionnaires. Results: There was no statistically significant difference between Group 1 and Group 2 in terms of the preoperative stage of uterine prolapse (2.6 (0.8) vs. 2.7 (0.7) [P=0.534]). The postoperative period was significantly longer in Group 1 compared to Group 2 (1,014.7 (348.8) days vs. 598.4 (276.5) days [P=0.013]). In the POP-Q evaluation, point C was measured as -6.6 (1.1) cm in Group 1 and -5.2 (1.5) cm in Group 2, indicating a statistically more proximal location (P=0.037). The total vaginal length was greater in Group 1 than in Group 2, but this difference was not statistically significant (8.7 (1.2) cm vs. 8.1 (1.3) cm, [P=0.343]). There was no statistical difference between the groups in terms of uterine prolapse stages and sexual function during the follow-up period. Conclusion: Laparoscopic lateral suspension is an alternative method for patients with uterine prolapse, offering comparable anatomical and sexual outcomes to laparoscopic sacrocolpopexy.